Physicians' Perceptions of Stakeholder Influence on Discharge Timing in a Children's Hospital - Lea M. Bornstein MD; Sara E. Landers MSW; Susan L. Rosenthal PhD; Teresa A. McCann MD (SAGE Publishing, 2019)
Attending physicians (N = 53) at a nonprofit, university-affiliated academic children's hospital completed a survey about how key stakeholders affect timing of patient discharge beyond attending assessment of medical stability. Physicians perceived families and hospital administration as more often having an impact on discharge timing than they should and perceived members of the care team and peer physicians/consultants as less frequently having an impact than they should. All but one physician reported discharging a patient either earlier or later than they felt was appropriate due to pressure from at least one stakeholder group; almost all physicians had done so in response to pressure from families. When physicians changed discharge timing based on stakeholder pressure, they tended to extend hospital stay except in the case of administrative pressure. These findings highlight the need for improvements in communication regarding discharge goals and for future research on how navigating competing interests affect physician stress.